2017
DOI: 10.1016/j.virol.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity detection and sorting of infectious human immunodeficiency virus (HIV-1) particles by flow virometry

Abstract: Detection of viruses by flow cytometry is complicated by their small size. Here, we characterized the ability of a standard (FACSAria II) and a sub-micron flow cytometer (A50 Micro) to resolve HIV-1 viruses. The A50 was superior at resolving small particles but did not reliably distinguish HIV-1, extracellular vesicles, and laser noise by light scatter properties alone. However, single fluorescent HIV-1 particles could readily be detected by both cytometers. Fluorescent particles were sorted and retained infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 55 publications
2
68
0
3
Order By: Relevance
“…Nanoscale flow cytometry (NFC), also called flow virometry, is a new and powerful tool in the field of virology that enables the phenotypic analysis of the markers at the surface of individual virions 11 , 25 32 . Virus populations can now be profiled and sorted in multi-parameter analyses, much in the same way as cells 25 , 27 , 30 , 32 , 33 . However, NFC analysis with current instrumentation can be challenging due to the fact that these particles are at the limit of detection for flow cytometers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoscale flow cytometry (NFC), also called flow virometry, is a new and powerful tool in the field of virology that enables the phenotypic analysis of the markers at the surface of individual virions 11 , 25 32 . Virus populations can now be profiled and sorted in multi-parameter analyses, much in the same way as cells 25 , 27 , 30 , 32 , 33 . However, NFC analysis with current instrumentation can be challenging due to the fact that these particles are at the limit of detection for flow cytometers.…”
Section: Introductionmentioning
confidence: 99%
“…This can be much lower than the published manufacturer’s specifications, but the onus falls on individual users to achieve this. Despite these caveats, several groups are currently using conventional flow cytometers originally designed for cells to analyze nanoparticles in the 90–150 nm size range 11 , 25 34 , 36 40 . Common instrument hardware additions for small particle detection include lasers with higher power and the use of photomultiplier tubes (PMTs) instead of photodiodes for forward scatter detection.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most viral suspensions are composed of distinct subpopulations, characterized, for example, by different size characteristics or expression of glycoproteins. Previous studies have shown that these viral subpopulations can demonstrate differences in infectivity (69). Although it is at this stage not possible to determine whether the fraction of mobile HSV-1 virions also presents higher infectivity, the high abundance of GAGs in the extracellular matrix and close to the cell surface could provide the means for HSV-1 diffusion in vivo.…”
mentioning
confidence: 97%
“…Despite these exciting initial reports, the analysis of viruses by flow cytometry, which Grivel and colleagues termed "flow virometry" in 2013 (14), has become more mainstream only recently. Flow virometry has now been used to characterize an expanding array of additional viruses, including lambda phage (15), herpes simplex virus 1 (HSV-1) (16,17), mouse hepatitis virus (MHV) (18), human immunodeficiency virus (HIV) (14,(19)(20)(21), Nipah virus (22), Junin virus (23), vaccinia virus (24), dengue virus (20,25), human cytomegalovirus (HCMV) (26), and giant viruses (13). Flow virometry is becoming a powerful tool to characterize viruses.…”
Section: The Birth Of Flow Virometrymentioning
confidence: 99%